DISCRETION FOR MINERAL AND COAL MANAGEMENT IN THE ERA OF REGIONAL AUTONOMY AND ITS IMPLICATION IN VIEW OF ARTICLE 33 PARAGRAPH (3) OF THE 1945 CONSTITUTION - Hayati, Tri (UI Scholars Hub, 2014)
Ever since the implementation of the regional governance reform era, fundamental changes have occurred in the discretion for the management of the mineral and coal mining sectors. The adoption of Law Number 22 Year 1999 led to the expansion of regional governments’ autonomy, applying autonomy in the broadest sense of the word, by focusing merely on ‘decentralization’, while disregarding the principle of de-concentration. Governmental affairs submitted based on decentralization refer to discretion by attribution, whereas de-concentration refers to discretion by delegation. Basically, all governmental affairs are submitted to the Regency and Municipality Government, except for 6 (six) matters which constitute the discretion of the central government. Discretion for the management of mining includes the discretion vested in the Regency and Municipality Government by virtue of Government Regulation Number 75 Year 2001. This implies that the concept of ‘control by the state’ (‘penguasaan negara’) as mandated in Article 33 of the 1945 Constitution of the State of the Republic of Indonesia has become degraded.